A sera-epidemiological study on pertussis immunity levels among community populations and an analysis of the underlying factors in Tianjin China. Issue 51 (16th December 2015) - Zhang, Ying; Huang, Haitao; Gao, Zhigang; Liu, Yong; Liu, Peng; Ding, Yaxing; Wang, Lijuan; Chen, Derong; Wu, Shuqing
Abstract: Background: The aim of this study is to characterize the sera-epidemiology of pertussis immunity levels among community populations and to identify the underlying factors. Moreover, our study will help resolve new issues encountered during the control and prevention of pertussis reemergence. Methods: The anti-pertussis antibody levels among community populations were examined using enzyme linked immunosorbent assays (ELISA) over three years. Comparative studies were carried out to assess the efficacy of different types of vaccines. Meanwhile, the duration of protection provided by DTaP within the under-7 age group was subjected to further analysis. Results: The average positive rate for anti-pertussis antibody was 49.15% across all community populations, among which the 4–12 age group showed a rate substantially lower than those of other groups ( P  < 0.001). There was no statistically significant difference in anti-pertussis antibody levels ( P  = 0.977) between people receiving three and four doses of the vaccine. The surveillance results showed that the positive antibody response rate elicited by component pertussis combo (DTcP) vaccines (84.44%) was strikingly higher than that elicited by acellular pertussis combo (DTaP) vaccines (37.22%, P  < 0.001). More specifically, when given 4 doses of DTcP vaccines, 66.67% of the people showed positive anti-pertussis toxin (PT) antibody levels, which was higher than the ratio of 9.87% ( P  < 0.001) in the case of DTaP vaccines. The positive anti-pertussis antibody levels peaked at 73% within the first five months following vaccination and then gradually decreased to below 20% in four years. The positive rate was inversely correlated with the length of time after vaccination ( r  = −0.929, P  = 0.003). Conclusions: The anti-pertussis antibody levels were not only relatively low among community populations, but also dropped excessively rapidly among vaccinated populations. Natural infection is an important contributor to the high pertussis immunity levels seen in adolescents and adults. The efficacy of DTaP remains to be improved.